2015
DOI: 10.4103/0259-1162.152148
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of levobupivacaine and levobupivacaine with fentanyl in infraumbilical surgeries under spinal anaesthesia

Abstract: Background:Intrathecal opioids added to low dose local anesthetics in spinal anaesthesia intensifies sensory block without affecting sympathetic blockade. Aim was to evaluate the safety and efficacy of intrathecal levobupivacaine plain versus levobupivacaine plus fentanyl in infraumbilical surgeries.Materials and Methods:In a prospective randomized double blind study, 100 patients of American Society of Anesthesiologists grades I and II of either sex, 20–65 years of age were included after approval from the Et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
(23 reference statements)
2
11
1
1
Order By: Relevance
“…Similarly Chattopadhyay et al concluded that addition of fentanyl to levobupivacaine does not increase the incidence of bradycardia. [9,10] Lee et al also further reported no significant difference in study groups in the hemodynamic changes, and the quality of sensory and motor block when 2.6ml of 0.5% levobupivacaine was compared with 2.3ml of 0.5% levobupivacaine with fentanyl 15µgm. [5] Owing to the lower affinity of the S (-) isomer to cardiac sodium channels compared to the R isomer, levobupivacaine is associated with less cardiac side effects.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly Chattopadhyay et al concluded that addition of fentanyl to levobupivacaine does not increase the incidence of bradycardia. [9,10] Lee et al also further reported no significant difference in study groups in the hemodynamic changes, and the quality of sensory and motor block when 2.6ml of 0.5% levobupivacaine was compared with 2.3ml of 0.5% levobupivacaine with fentanyl 15µgm. [5] Owing to the lower affinity of the S (-) isomer to cardiac sodium channels compared to the R isomer, levobupivacaine is associated with less cardiac side effects.…”
Section: Discussionmentioning
confidence: 96%
“…Opioids are hypobaric and when added to a hypobaric solution will make the mixture more hypobaric thus altering the density of resulting solution which effects the direction and spread of local anaesthetic. [9] It has been suggested that 0.5% levobupivacaine, i.e. 5mg/ml, will contain 13% more local anaesthetic than 0.5% racemic bupivacaine, because this corresponds with milligrams of bupivaciane-hydrochloride per milliliter.…”
Section: Discussionmentioning
confidence: 99%
“…A higher sensory level was achieved and the shorter motor block ensured that patients could be made to mobilize earlier in daycare urological procedures. 12,25 Akan et al 4 combined lower dose levobupivacaine with fentanyl and sufentanil which provided faster onset of sensorial block, lower frequency and shorter duration of motor block, and longer analgesia time in TURP under spinal anesthesia. In our study, however, analgesia time was longer in the plain levobupivacaine group but onset of sensory action was hastened by the addition of fentanyl.…”
Section: 21mentioning
confidence: 99%
“…This may prove beneficial for ambulatory surgeries. [10][11][12] Lipophilic opioids (e.g., fentanyl and sufentanil) are increasingly being administered intrathecally as adjuncts to local anesthetics. 4,13 The literary evidence has established that addition of opioids provides a dose-sparing effect of levobupivacaine, with improved quality of the block and less hemodynamic variations during perioperative period.…”
Section: Introductionmentioning
confidence: 99%
“…The results of our study in term of sensory characteristics have supported the findings of previous studies. [17][18][19][20][21][22] But, considering the duration of surgery in both the groups, levobupivacaine alone would be adequate for intrathecal block for elective caesarean deliveries.…”
Section: Figure 2 Intraoperative Changes In Systolic Blood Pressure mentioning
confidence: 99%